Freezing Method for Rock Cross-Cut Coal Uncovering: Aging Characteristic of Effective Freezing Distance on Injecting Liquid Nitrogen into Coal Seam - Heyi Ma; Chuanqu Zhu; Pengtao Zhao; Binbin Wang (Advances in Civil Engineering)
Based on artificial freezing engineering practice, the comprehensive technology is suggested to realize safe and fast rock cross-cut coal uncovering, which mainly includes four steps of drilling, water injection wetting coal, gas drainage, and injection liquid nitrogen into coal seam. Freezing test of liquid nitrogen injection into coal is carried out to obtain the cooling curves, and comparing the test results, the numerical inverse method is applied to determine the thermal conductivity of coal seam. Then, the model of injecting liquid nitrogen into coal seam is established to simulate and analyze the aging characteristic of effective freezing radius. The results show that the thermal conductivity of wetting coal increases linearly with temperature decreasing. The periodic method with 8h intervals can be adopted to inject liquid nitrogen into coal seam, and the freezing wall is formed around the injection hole. With the increase of freezing time, the effective freezing radius (below 273.15 K) increases by power exponent, and the freezing speed in coal seam decreases gradually. This result will provide a theoretical basis for layout optimization of injection holes in rock cross-cut coal uncovering.